If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 7 = -1(x + -2) Reorder the terms: 7 + y = -1(x + -2) Reorder the terms: 7 + y = -1(-2 + x) 7 + y = (-2 * -1 + x * -1) 7 + y = (2 + -1x) Solving 7 + y = 2 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + y = 2 + -7 + -1x Combine like terms: 7 + -7 = 0 0 + y = 2 + -7 + -1x y = 2 + -7 + -1x Combine like terms: 2 + -7 = -5 y = -5 + -1x Simplifying y = -5 + -1x
| 2x+6=-2x | | y+5=-6(x-7) | | 8x+9x=275 | | -17x+29y=23 | | sin(5x)+cos(4x)=2 | | (2x-1)(2x-1)-(3x+2)(3x+2)+5(x-3)(x+3)=1 | | 2x^2-10x-3x^2=26 | | x²-3x=-5/4 | | 888888888/12345679 | | x^2+20x-420=0 | | 20+4y=2 | | 20+y=36 | | 7/2*3/8 | | Graphy=-9x^2 | | 14=-x-y | | 5x+5y=38 | | -7+4+(-6)= | | 6x+0+6x+24=96 | | 4(v+9)=6v+24 | | Sin^2(x)cos^2(x)=0 | | 3x+226=79x-6 | | Cosx=cotx(tanx) | | 10/3x=-5/6 | | Cosx=cotx(secx) | | x^7=0.01 | | Cosx=cotx(sinx) | | Cosx=cotx(y) | | -8y+5=-67 | | 8/2=-a/9 | | 1+x/6=-3 | | 9x-20+9x-48=58 | | (2x+3)(6x+32)= |